Malaysian Mainstream And Alternative Online Newspaper Representations Of Risks From Lynas Rare Earth Project In Pahang, Malaysia - Dauda, Sharafa (2018)
This study purposively explores representations of risks from Lynas Advanced Materials Plant (LAMP) in six Malaysian online newspapers (The Star, New Straits Times, The Edge Markets, Malaysiakini, The Malaysian Insider and Free Malaysia Today). Discourse on the LAMP’s risks was pervasive in online news after report in the New York Times highlighted that, an Australian company was granted licence in 2012 to import and process rare earth in Kuantan. The aim of this study is to explain the role of the media in the amplification and attenuation of risks from the LAMP. A total of 1,167 news articles were content analysed and two journalists were interviewed. Coding of data was guided by two frameworks – the Social Amplification of Risks Framework and the Social Semiotic Theory of Multimodality using thematic analyses and van Dijk’s discursive strategies. The research found seven types of risks (environmental, financial, health, occupational, property, radioactive, technological); and connections between environmental, financial, radioactive and health risks. Radioactive risk was repeatedly intertwined with other risks and was a key ingredient and major agent of amplification to direct public attention toward radioactive risk from the LAMP. Three categories of news sources – known, known/unknown and unknown emerged against the two categories in existing literature, but known sources predominated. A handful of news sources (NGOs, professional and trade organisations, residents, opposition and Malaysian government) defined risks from the LAMP in terms of health, though residents’definition also covered environmental and financial risks. Furthermore, alternative online newspapers amplified all seven risk types against mainstream’s five. Thus, the alternative online newspapers provided diverse coverage than the mainstream. Likewise, journalists’ roles in amplifying or attenuating risks included: using multiple sources, (non)fact-checking, (non)filtering risk information, decoding risk information and (non)application of journalism ethics. Modes used to amplify, or attenuate risks were: colour, illustration, image, writing; and these occurred within cultural, social, financial, hazardous, historical and political contexts. Discursive devices used to convey meaning were history as a lesson, situation description, number game, dramatisation, irony, counter-factual and repetition. The information and transmission mechanisms used included: politicisation, advocacy campaigns, allegations/brickbats and discursive devices. Overall, this study revealed that risk representation from rare earth in a digital news environment is multidimensional and intensified or weakened in a multi-layered discourse. The stakeholders are engaged in a contestation by positioning their narratives to oppose or support their interests, which are amplified or attenuated by the online newspapers as social amplification stations.